Visualization of a scale free network in a smartphone-based multimedia big data environment - Ahmad, Akhlaq; ., Md. Abdur Rahman; Sadiq, Bilal; Mohammed, Shady; Basalamah, Saleh; Wahiddin, Mohamed Ridza (IEEE, 2015)
Smartphones equipped with varieties of sensors enable them in participatory and opportunistic crowd-sourced sensing. The built-in as well as external sensors paired with modern smartphones provide an ideal multimedia big data source, where a very large crowd can share audio, video, text, SMS, location, etc. In this paper, we will illustrate our proposed big data framework that has been storing multimedia data from a very large crowd since September 2014. Our framework uses Scale Free Network (SFN) to represent the dynamics of large crowd and produces visualization metrics by running spatio-temporal queries over the proposed multimedia big data framework.